Personality traits and reasons for residential mobility: Longitudinal data from United Kingdom, Germany, and Australia - Jokela, Markus (My University, 2021)
Personality traits have been associated with differences in residential mobility, but details are lacking on the types of residential moves associated with personality differences. The present study pooled data from four prospective cohort studies from the United Kingdom (UK Household Longitudinal Survey, and British Household Panel Survey), Germany (Socioeconomic Panel Study), and Australia (Household, Income, and Labour Dynamics in Australia) to assess whether personality traits of the Five Factor Model are differently related to residential moves motivated by different reasons to move: employment, education, family, housing, and neighborhood (total n = 86,073). Openness to experience was associated with all moves but particularly with moves due to employment and education. Extraversion was associated with higher overall mobility, except for moves motivated by employment and education. Lower emotional stability predicted higher probability of moving due to neighborhood, housing, and family, while higher agreeableness was associated with lower probability of moving due to neighborhood and education. Adjusting for education, household income, marital status, employment status, number of children in the household, and housing tenure did not substantially change the associations. These results suggest that different personality traits may motivate different types of residential moves.
Personality and Individual Differences
Keywords: Culture and language; Housing, communities and neighbourhoods